Strategies for boosting students’ enrolment into business education programme of colleges of education - Clever Omovigho Igberaharha; Moses Onyesom (International Journal of Evaluation and Research in Education (IJERE), 2021)
A close observation in recent times has shown a steady decline of students’ enrolment into business education programme especially in the colleges of education. The situation is becoming worrisome considering the social implications it has on the education industry. Thus, the study was conducted to determine strategies for boosting students’ enrolment into business education programme of colleges of education in Delta State.  Design of this research was descriptive survey and 118 business education lecturers in the colleges of education in Delta State participated in the survey. Data were collected with questionnaire. The results of data analysis showed that the respondents agreed that the attracting and retaining strategies considered in the study were necessary frameworks for boosting students’ enrolment into business education programme. The test of hypotheses showed that irrespective of the years of work experience of the respondents, their responses did not differ significantly. This indicated that the examined attracting and retaining strategies were critical for boosting students’ enrolment. It was concluded that the attracting and retaining strategies determined by the study are effective means of reversing the steady decline of students’ enrolment experienced in recent years at the colleges of education in Delta State, Nigeria.